The Urgency of Limiting Procedural Democracy for Handling Pandemic in Indonesia [Urgensi Limitasi Demokrasi Prosedural Bagi Penanganan Pandemi di Indonesia] - Pratama, Aprilianto Satria (Jurnal Politica, 2022)
It is undeniable that the handling of the pandemic in almost all countries in the world has been framed by Joseph Alois Schumpeter’s conception of procedural democracy, which focuses on procedural elements in the formulation of the common good. One of the reason is because the majority of countries in the world choose to handle the pandemic in a monocentricprocedural method, thus ignoring society participation and initiatives. In fact, it is the society who, in many situations, have an idea of handling the pandemic more practically. Therefore, taking the practice of handling the pandemic in Indonesia as an example, this paper is here to dissect the implementation of the procedural democratic conception in the field. Through a qualitative literature study and guided by the research question: “how is the practice of limiting procedural democracy in handling the pandemic in Indonesia?”, this paper then comes to the following conclusions. First, it is true that procedural democracy has become a crucial framework for the country in dealing with the pandemic. Second, however, procedural democracy also has the potential to produce a negative impact on the relationship between demos and kratos. Third, therefore, the limitations on procedural democracy are urgently needed.AbstrakTidak bisa dipungkiri bahwa penanganan pandemi di hampir seluruh negara di dunia banyak dikerangkai oleh konsepsi demokrasi prosedural Joseph Alois Schumpeter, yang menitik beratkan substansinya pada unsur-unsur prosedural dalam perumusan common good. Adapun situasi ini terjadi, salahsatunya karena mayoritas negara di dunia memilih untuk menangani pandemi secara monosentris-prosedural sehingga mengabaikan partisipasi dan inisiatif masyarakat. Padahal, masyarakatlah yang, dalam banyak situasi, memiliki gambaran tentang penanganan pandemi secara lebih praktikal. Oleh karenanya, mengambil praktik penanganan pandemi di Indonesia sebagai contoh, tulisan ini hadir untuk membedah penyelenggaraan konsepsi demokrasi prosedural tersebut di lapangan. Melalui studi pustaka kualitatif dan dipandu oleh pertanyaan penelitian: “bagaimana praktik limitasi demokrasi prosedural dalam penanganan pandemi di Indonesia?”, tulisan ini lantas sampai pada beberapa kesimpulan sebagai berikut. Pertama, benar bahwa demokrasi prosedural telah menjadi kerangka krusial bagi negara dalam menangani pandemi. Kedua, meski demikian, demokrasi prosedural juga berpotensi memproduksi dampak negatif bagi relasi antara demos dan kratos. Ketiga, oleh karenanya, limitasi atas demokrasi prosedural jadi mendesak untuk diselenggarakan.